Belanjahalal.id: Halal E-Commerce Solution Model for Muslims Society - Agnisa Widayanti; Febrika Yogie Hermanto; Novia Indrawati (Sekolah Tinggi Agama Islam Almuhammad Cepu, 2022)
The purpose of this paper is to offer a halal e-commerce model for Muslims. The design of this paper is extant literature on the (i) non-halal e-commerce faced by Muslims in Indonesia, and (ii) e-commerce have been reviewed critically and used in the attempt of proposing a halal model. This paper has developed halal e-commerce as a solution for Muslims to trade using e-commerce. This paper is based on conceptual explorations of literature in the area of halal e-commerce. This is a conceptual paper, so it did not employ any empirical analysis. The finding of this paper will provide a solution for Muslims who wants to trade in the e-commerce sector without any doubt of haram issues. This paper has provided an alternative model for e-commerce in the form of halal models. The model of belanjahalal.id was developed by incorporating halal concepts such as types of murabahah, salam, istishna ' and transaction terms following Islamic law.